2020
DOI: 10.3390/jof6030139
|View full text |Cite
|
Sign up to set email alerts
|

Role of Voriconazole in the Management of Invasive Central Nervous System Aspergillosis: A Case Series from a Tertiary Care Centre in India

Abstract: Invasive central nervous system (CNS) aspergillosis is acquired by either hematogenous dissemination or direct spread from a sinus infection. We describe a series of nine patients with CNS aspergillosis from a tertiary care teaching institute in North India who were treated with voriconazole alone or in combination with surgery. All patients who had clinical and radiological features consistent with fungal CNS infection, showed the presence of septate hyphae on histopathology/microscopy and were either culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
(75 reference statements)
0
7
0
2
Order By: Relevance
“…Several other studies found that the outcome is better with voriconazole. 8,16,23,28 Indirect evidence for the superiority of azoles is seen in the successful outcomes with azoles following failure of amphotericin therapy. 7,28 Liposomal amphotericin B, which has less toxicity, has been recommended as alternative primary therapy only in patients with hepatic impairment or where drug interactions necessitate alternatives to azoles.…”
Section: Mixed Fungal Sinusitis and Conversion Of Cgfs To Noninvasive...mentioning
confidence: 99%
“…Several other studies found that the outcome is better with voriconazole. 8,16,23,28 Indirect evidence for the superiority of azoles is seen in the successful outcomes with azoles following failure of amphotericin therapy. 7,28 Liposomal amphotericin B, which has less toxicity, has been recommended as alternative primary therapy only in patients with hepatic impairment or where drug interactions necessitate alternatives to azoles.…”
Section: Mixed Fungal Sinusitis and Conversion Of Cgfs To Noninvasive...mentioning
confidence: 99%
“…This species is the second leading cause of invasive aspergillosis and is associated with approximately 10% of bronchopulmonary aspergillosis [ 64 ]. It may cause various diseases, including keratomycosis [ 65 ] and endophthalmitis [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…[7] Vorikonazol mempunyai daya penetrasi yang baik terhadap sawar darah otak sehingga vorikonazol menjadi terapi pilihan untuk aspergilosis intrakranial. [19,20] Literatur menunjukkan mayoritas pasien yang mendapatkan vorikonazol sebagai pilihan pertama pengobatan mengalami perbaikan. [7] Pada sebuah penelitian dari 123 kasus dengan aspergilosis SSP, didapatkan mortalitas pada kelompok monoterapi amfoterisin B lebih tinggi dibandingkan monoterapi vorikonazol (63 vs 35%).…”
Section: Pembahasanunclassified
“…[7] Pada sebuah penelitian dari 123 kasus dengan aspergilosis SSP, didapatkan mortalitas pada kelompok monoterapi amfoterisin B lebih tinggi dibandingkan monoterapi vorikonazol (63 vs 35%). [20] Vorikonazol menghambat biosintesis ergosterol yang merupakan komponen penting membran sel jamur sehingga mengganggu pertumbuhannya. [21] Vorikonazol dapat diberikan secara intravena maupun per oral.…”
Section: Pembahasanunclassified